2019
DOI: 10.1097/inf.0000000000002221
|View full text |Cite
|
Sign up to set email alerts
|

Measles Hospitalizations at a United States Children’s Hospital 2011–2017

Abstract: Background: There are no recent descriptions of measles hospitalizations and complications in US children despite outbreaks within the past decade—including 2 in Minnesota (2011 and 2017). The objective of our study was to describe complications, hospital management and resource utilization for children hospitalized for measles at a US children’s hospital. Methods: Retrospective case series of children (0–18 years of age) hospitalized for measles (obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
12
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 36 publications
6
12
1
1
Order By: Relevance
“…Regarding laboratory parameters of hospitalized children with measles, there was a significant number of children with mild (26%) or severe (3.8%) hyponatremia at presentation, a finding that is not regularly described. Elevated transaminases were detected in 40.6% of measles cases, which was also found in other studies [29,31].…”
Section: Plos Onesupporting
confidence: 87%
See 1 more Smart Citation
“…Regarding laboratory parameters of hospitalized children with measles, there was a significant number of children with mild (26%) or severe (3.8%) hyponatremia at presentation, a finding that is not regularly described. Elevated transaminases were detected in 40.6% of measles cases, which was also found in other studies [29,31].…”
Section: Plos Onesupporting
confidence: 87%
“…In the present study a high hospitalization rate of 59.2% was found, but rates lower than 20%, or higher than 60% have also been reported [11,12,17,25,29,30]. This wide range of hospitalization rates worldwide may be related to differences in management and surveillance systems, health policies and the affected age groups.…”
Section: Plos Onesupporting
confidence: 40%
“…From 1996 to 2002 measles hospitalizations were at an all-time low in US history with an estimated �23 cases annually [27]. While more recent data is lacking, an analysis of measles hospitalizations in a single children's hospital in Minnesota from 2011-2017 showed 33 total cases, driven largely by a 2017 outbreak in the Somali-American community [30]. Despite measles being officially declared eliminated from the US in 2000 [23,24], this study found 1,018 weighted hospitalizations for measles (mean of 68 cases per year) and rising number of measles hospitalizations from 2002-2016.…”
Section: Discussionmentioning
confidence: 99%
“…The average cost per measles-related hospitalization was $7,438 with total cost from 2002-2016 of $16,973,795. There was an estimated $10,000 cost per hospitalization during the 1989-1991 US measles outbreak [11], and while recent cost estimates are limited, the median cost per measles hospitalization in a single children's hospital from 2011-2017 was $5,291 [30]. Measles hospitalization costs include infection control required to stop nosocomial spread, such as isolation precautions, testing of exposed individuals, vaccine/immunoglobulin administration, tracing of cases, and the personnel hours required to carry out these tasks [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, these types of financial penalties may also be fair because it is clear that persons unvaccinated by parental choice place an unneeded financial burden on our health care system. [7][8][9] A limitation is that this study was limited to European Union member states, Norway, and Iceland, which leaves out several European countries that have had high rates of measles in recent years (Ukraine, in particular). 10 A strength of the study was adjusting for several covariates likely to impact vaccination uptake to better understand the consequences of these policies.…”
mentioning
confidence: 99%